Respiratory Virus Detection and Sequencing from SARS-CoV-2–Negative Rapid Antigen Tests - Emmanuela Jules; Charlie Decker; Brianna Jeanne Bixler; Alaa Ahmed; Zijing (Carol) Zhou; Itika Arora; Henok Tafesse; Hannah Dakanay; Andrei Bombin; Ethan Wang; Jessica Ingersoll; Kathy Bifulco; et al. (Emerging Infectious Diseases)
Genomic epidemiology offers insight into the transmission and evolution of respiratory viruses. We used metagenomic sequencing from negative SARS-CoV-2 rapid antigen tests to identify a wide range of respiratory viruses and generate full genome sequences. This process offers a streamlined mechanism for broad respiratory virus genomic surveillance.